2009
DOI: 10.1209/0295-5075/86/40008
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the spontaneous spiking regularity via channel blocking on Newman-Watts networks of Hodgkin-Huxley neurons

Abstract: We investigate the regularity of spontaneous spiking activity on Newman-Watts small-world networks consisting of biophysically realistic Hodgkin-Huxley neurons with a tunable intensity of intrinsic noise and fraction of blocked voltage-gated sodium and potassium ion channels embedded in neuronal membranes. We show that there exists an optimal fraction of shortcut links between physically distant neurons, as well as an optimal intensity of intrinsic noise, which warrant an optimally ordered spontaneous spiking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 44 publications
1
49
0
7
Order By: Relevance
“…8,[10][11][12] Array-enhanced coherence resonance is found in an array of coupled FitzHugh-Nagumo neurons. 8,9 For more complex coupling, optimal configuration of network exists when predefined topology structures are given [13][14][15][16] or self-organized connections are developed based on spike-timing-dependent plasticity (STDP) learning rules. 17 Multilayer feedforward network (FFN) structure, which is one of the most extensively studied network structure, can characterize the properties of spiking activities in propagation.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] Array-enhanced coherence resonance is found in an array of coupled FitzHugh-Nagumo neurons. 8,9 For more complex coupling, optimal configuration of network exists when predefined topology structures are given [13][14][15][16] or self-organized connections are developed based on spike-timing-dependent plasticity (STDP) learning rules. 17 Multilayer feedforward network (FFN) structure, which is one of the most extensively studied network structure, can characterize the properties of spiking activities in propagation.…”
Section: Introductionmentioning
confidence: 99%
“…neuronal dynamics [37], only that here this is additionally amplified by the scale-free interaction structure. Indeed, as Fig.…”
mentioning
confidence: 78%
“…The relevance of ion channel noise can also be studied by means of computational models. It is known, for example, that the regularity of spontaneous spike trains can be reduced or enhanced by blocking or poisoning some fraction of sodium or potassium ion channels [34,35], and also that channel blocking can enhance the collective spiking regularity of bi-directionally coupled [36] and small-world neuronal networks [37]. Recently, the development, propagation or robustness of spiral waves observed in the cortex of brain has been addressed via ion channel poisoning [38][39][40].…”
mentioning
confidence: 99%
“…Since a regular network may be biologically questionable due to the brain's sophisticated anatomical structure, random network topologies have been proposed to bridge the gap between artificial and brain networks. In this context, the small-world network topology, proposed by Watts and Storgatz [5], is one of the best models to reflect the functional connectivity and anatomic structure of the brain [6][7][8][9][10][11][12][13]. Moreover, many recent investigations showed that real-life networks such as the World Wide Web, protein interaction networks, email networks, social networks, and metabolic networks, exhibit the small-world property [14][15][16].…”
Section: Introductionmentioning
confidence: 99%